2014
DOI: 10.1051/0004-6361/201322140
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-UV spectroscopy of interstellar ice analogs

Abstract: Context. The vacuum-UV (VUV) absorption cross sections of most molecular solids present in interstellar ice mantles with the exception of H 2 O, NH 3 , and CO 2 have not been reported yet. Models of ice photoprocessing depend on the VUV absorption cross section of the ice to estimate the penetration depth and radiation dose, and in the past, gas phase cross section values were used as an approximation. Aims. We aim to estimate the VUV absorption cross section of molecular ice components. Methods. Pure ices com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 50 publications
3
95
0
Order By: Relevance
“…(Cruz-Diaz et al 2014a,b) Recently, Chen et al (2014) showed that the differences in CO photodesorption rates reported by various groups over the past decade may be partly explained by differences in MDHL emission spectra. Carbon monoxide is an excellent example, since it strongly absorbs 160 nm photons while Lyman-α photons are clearly off resonance, as has been shown in independent experiments (Fayolle et al 2011;Cruz-Diaz et al 2014a).…”
Section: Introductionmentioning
confidence: 74%
“…(Cruz-Diaz et al 2014a,b) Recently, Chen et al (2014) showed that the differences in CO photodesorption rates reported by various groups over the past decade may be partly explained by differences in MDHL emission spectra. Carbon monoxide is an excellent example, since it strongly absorbs 160 nm photons while Lyman-α photons are clearly off resonance, as has been shown in independent experiments (Fayolle et al 2011;Cruz-Diaz et al 2014a).…”
Section: Introductionmentioning
confidence: 74%
“…It is interesting to note that the ultraviolet experiment could not have been performed using Lyα photons because at that wavelength the CO ice does not absorb significantly. Most likely, CO absorption occurred at longer wavelengths in the microwave-discharge hydrogen lamp spectrum, around 8.6eV, where the CO absorption crosssection is a factor of 2 larger than the value reported in Loeffler et al (2005);see Cruz-Diaz et al (2014) for details.…”
Section: Comparison With Other Experimentsmentioning
confidence: 83%
“…Vacuum ultraviolet studies show that CO ice is not efficiently dissociated at photon energies below 11 eV, and therefore photodesorption is the main effect (e.g., Muñoz Caro et al 2010). The photoabsorption crosssection of CO has been measured by Cruz-Diaz et al (2014). They found CO to be relatively transparent to Lyα radiation, absorbing preferentially in the 140-160 nm spectral range.…”
Section: Comparison With Other Experimentsmentioning
confidence: 99%
“…The UV spectrum provided by this lamp consists of a strong Ly-α (121.6 nm) emission and a series of H 2 transition bands in the 155-165 nm range , with an estimated flux of ∼2 × 10 15 photons cm −2 s −1 (Warnek 1962). The light emitted by such a lamp is a good analog to the UV radiation field found in many astrophysical environments including the dense ISM and protostars (d 'Hendecourt et al 1986;Allamandola et al 1988;Bernstein et al 1995;Cruz-Diaz et al 2014). In this work, the photon doses received by the samples were either 0.25 photons molecule −1 (hereafter referred to as the lower UV dose) or 0.70 photons molecule −1 (hereafter referred to as the higher UV dose).…”
Section: Irradiation Of Icesmentioning
confidence: 96%